Lowered Respiratory Response to Adenosine Diphosphate of Mitochondria Isolated from a Mutant B Strain of Schizophyllum commune - Hoffman, Robert M. (1972)
Mitochondria were isolated from the mycelium of a B-factor mutant in Schizophyllum commune that was previously shown to have its energy metabolism partially uncoupled. These mitochondria were compared to mitochondria isolated from wild-type mycelia and were found to increase their respiration rate upon addition of adenosine diphosphate to only one-half the extent of the mitochondria of wild-type mycelia.